The BlueScreen HC assay to predict the genotoxic potential of fragrance materials. (18th March 2022) - Thakkar, Yax; Joshi, Kaushal; Hickey, Christina; Wahler, Joseph; Wall, Brian; Etter, Sylvain; Smith, Benjamin; Griem, Peter; Tate, Matthew; Jones, Frank; Oudraogo, Gladys; Pfuhler, Stefan; et al.
Abstract: BlueScreen HC is a mammalian cell-based assay for measuring the genotoxicity and cytotoxicity of chemical compounds and mixtures. The BlueScreen HC assay has been utilized at the Research Institute for Fragrance Materials in a safety assessment program as a screening tool to prioritize fragrance materials for higher-tier testing, as supporting evidence when using a read-across approach, and as evidence to adjust the threshold of toxicological concern. Predictive values for the BlueScreen HC assay were evaluated based on the ability of the assay to predict the outcome of in vitro and in vivo mutagenicity and chromosomal damage genotoxicity assays. A set of 371 fragrance materials was assessed in the BlueScreen HC assay along with existing or newly generated in vitro and in vivo genotoxicity data. Based on a weight-of-evidence approach, the majority of materials in the data set were deemed negative and concluded not to have the potential to be genotoxic, while only a small proportion of materials were determined to show genotoxic effects in these assays. Analysis of the data set showed a combination of high positive agreement but low negative agreement between BlueScreen HC results, in vitro regulatory genotoxicity assays, and higher-tier test results. The BlueScreen HC assay did not generate any false negatives, thereby providing robustness when utilizing it as a high-throughput screening tool to evaluate the large inventory of fragrance materials. From the perspective of protecting public health, it is desirable to have no or minimal false negatives, as a false-negative result may incorrectly indicate the lack of a genotoxicity hazard. However, the assay did have a high percentage of false-positive results, resulting in poor positive predictivity of the in vitro genotoxicity test battery outcome. Overall, the assay generated 100% negative predictivity and 3.9% positive predictivity. In addition to the data set of 371 fragrance materials, 30 natural complex substances were evaluated for BlueScreen HC, Ames, and in vitro micronucleus assay, and a good correlation in all three assays was observed. Overall, while a positive result may have to be further investigated, these findings suggest that the BlueScreen HC assay can be a valuable screening tool to detect the genotoxic potential of fragrance materials and mixtures.